PENGARUH KERAGAMAN GENDER DAN USIA PEJABAT PERBENDAHARAAN TERHADAP PENYERAPAN ANGGARAN SATUAN KERJA (STUDI EMPIRIS PADA SATUAN KERJA LINGKUP PEMBAYARAN KPPN SEMARANG I) - Noviwijaya, Amdi; Rohman, Abdul (Diponegoro Journal of Accounting, 2013)
This study aims to examine the effect of a working unit treasury officers (KPA, PPK, PPSPM, Bendahara) gender diversity and age diversity on budget absorption. This study population consists of 155 working units which included in payment scope of KPPN Semarang One. Whereas the final sample of the present study consists of 120 working units which selected by Random Sampling Method. T Statistic Test was used to test the hypothesis. This study finds that gender diversity statistically have significant negative effect on budget absorption. Whereas age diversity statistically have significant positive effect on budget absorption. It provides evidence that young people are associated with improved performance.